Social and political foundations of constitutions - Galligan, D. J. (Denis James), 1947-; Versteeg, Mila, 1983- (Comparative constitutional law and policy., 2013)
"This volume analyses the social and political forces that influence constitutions and the process of constitution making. It combines theoretical perspectives on the social and political foundations of constitutions with a range of detailed case studies of constitution making in nineteen different countries. In the first part of the volume, leading scholars analyse and develop a range of theoretical perspectives, including constitutions as coordination devices, mission statements, contracts, products of domestic power play, transnational documents, and as reflection of the will of the people. In the second part of the volume, these theories are examined through in-depth case studies of the social and political foundations of constitutions in countries such as Egypt, Nigeria, Japan, Romania, Bulgaria, New Zealand, Israel, Argentina, and others. The result is a multidimensional study of constitutions as social phenomena and their interaction with other social phenomena. The approach combines social science analysis of the nature of constitutions with case studies of selected constitutions"--